Acceptance of COVID-19 vaccination in a sample of Middle Eastern and North African (MENA) Houston residents. - Fatin Atrooz; Zahra Majd; Ghalya Alrousan; Sarah Zeidat; Nadia N Abuelezam; Susan Abughosh; Samina Salim (Public Library of Science (PLoS), 2023)
Background COVID-19 vaccination has averted a significant number of deaths in the United States, but vaccination hesitancy continues to be a problem. Therefore, examining vaccination acceptance and/or hesitancy in local communities is critical. Methods A quantitative survey and a multivariable logistic regression model was utilized to determine predictors of COVID-19 vaccination in Middle Eastern and North African (MENA) origin Houston residents. The outcome of interest was COVID-19 vaccination status (vaccinated versus not vaccinated). Covariates included: demographics, health, and COVID-19 factors. Statistical analyses included SAS version 9.4 at a priori significance level of 0.05. Results The overall vaccine acceptance rate was significantly high in this population subset (N = 366), with 77.60% vaccinated, and 22.40% not vaccinated. MENA individuals with some college degrees were less likely to report vaccination than those with a graduate degree [Odds Ratio (OR): 0.18; 95% Confidence Interval (CI): 0.04, 0.77]. Homeowners were more likely to get vaccinated than renters (OR: 2.58; 95%CI: 1.17, 5.68). Individuals practicing Islamic faith were more likely to get vaccinated than other religious affiliations (OR: 3.26; 95%CI: 1.15, 9.19). Individuals with hypertension were less likely to get vaccinated than those without it (OR: 0.34; 95%CI: 0.13, 0.92), and those with anxiety were more likely to get vaccinated than those without anxiety (OR: 4.23; 95%CI: 1.68, 10.64). Conclusions Health status, education level, financial stability, and religious affiliation are some of the determining factors that potentially influence vaccination acceptance/hesitancy among the MENA community.